Effects of Propranolol on Bone, White Adipose Tissue, and Bone Marrow Adipose Tissue in Mice Housed at Room Temperature or Thermoneutral Temperature - Turner, Russell T.; Philbrick, Kenneth A.; Wong, Carmen P.; Gamboa, Amanda R.; Branscum, Adam J.; Iwaniec, Urszula T. (Frontiers in Endocrinology, 2020)
Growing female mice housed at room temperature (22°C) weigh the same but differ in body composition compared to mice housed at thermoneutral (32°C). Specifically, mice housed at room temperature have lower levels of white adipose tissue (WAT). Additionally, bone marrow adipose tissue (bMAT) and cancellous bone volume fraction in distal femur metaphysis are lower in room temperature-housed mice. The metabolic changes induced by sub-thermoneutral housing are associated with lower leptin levels in serum and higher levels of Ucp1 gene expression in brown adipose tissue. Although the precise mechanisms mediating adaptation to sub-thermoneutral temperature stress remain to be elucidated, there is evidence that increased sympathetic nervous system activity acting via β-adrenergic receptors plays an important role. We therefore evaluated the effect of the non-specific β-blocker propranolol (primarily β1andβ2antagonist) on body composition, femur microarchitecture and bMAT in growing female C57BL/6 mice housed at either room temperature or thermoneutral temperature. As anticipated, cancellous bone volume fraction, WAT and bMAT were lower in mice housed at room temperature. Propranolol had small but significant effects on bone microarchitecture, (increased trabecular number and decreased trabecular spacing) but did not attenuate premature bone loss induced by room temperature housing. In contrast, propranolol treatment prevented housing temperature-associated differences in WAT and bMAT. To gain additional insight, we evaluated a panel of genes in tibia, using an adipogenesis PCR array. Housing temperature and treatment with propranolol had exclusive as well as shared effects on gene expression. Of particular interest was the finding that room temperature housing reduced, whereas propranolol increased, expression of the gene for acetyl-CoA carboxylase (Acacb), the rate-limiting step for fatty acid synthesis and a key regulator of β-oxidation. Taken together, these findings provide evidence that increased activation of β1 and/or β2 receptors contributes to reduced bMAT by regulating adipocyte metabolism, but that this pathway is unlikely to be responsible for premature cancellous bone loss in room temperature-housed mice.